A survey and stakeholder consultation of Independent Domestic Violence Advisor (IDVA) programmes in English maternity services - Camilla Forbes; Hayley Alderson; Jill Domoney; Alexandra Papamichail; Vashti Berry; Ruth McGovern; Nick Sevdalis; Judith Rankin; Mary Newburn; Andy Healey; Abigail Easter; Margaret Heslin; et al. (BMC, 2023)
Abstract Background Healthcare-based Independent Domestic Violence Advisors (hIDVA) are evidence-based programmes that provide emotional and practical support to service users experiencing domestic abuse. hIDVA programmes are found to improve health outcomes for service users and are increasingly delivered across a range of healthcare settings. However, it is unclear how hIDVA programmes are implemented across maternity services and the key facilitators and barriers to their implementation. The aim of this study was to identify; how many English National Health Service (NHS) Trusts with maternity services have a hIDVA programme; which departments within the Trust they operate in; what format, content, and variation in hIDVA programmes exist; and key facilitators and barriers of implementation in maternity services. Methods A national survey of safeguarding midwives (Midwives whose role specifically tasks them to protect pregnant women from harm including physical, emotional, sexual and financial harm and neglect) within all maternity services across England; descriptive statistics were used to summarise responses. A World Café event (a participatory method, which aims to create a café atmosphere to facilitate informal conversation) with 38 national key stakeholders to examine barriers and facilitators to hIDVA programme implementation. Results 86/124 Trusts (69%) with a maternity service responded to the survey; 59(69%) of respondents reported that they had a hIDVA programme, and 47(55%) of the hIDVA programmes operated within maternity services. Key facilitators to implementation of hIDVA programmes included training of NHS staff about the hIDVA role and regular communication between Trust staff and hIDVA staff; hIDVA staff working directly from the Trust; co-creation of hIDVA programmes with experts by experience; governance and middle- and senior-management support. Key barriers included hIDVA staff having a lack of access to a private space for their work, insecure funding for hIDVA programmes and issues with recruitment and retention of hIDVA staff. Conclusions Despite hIDVA programmes role in improving the health outcomes of service users experiencing domestic abuse, increased funding and staff training is needed to successfully implement hIDVA staff in maternity services. Integrated Care Board commissioning of acute and mental health trust services would benefit from ensuring hIDVA programmes and clinician DVA training are prioritised.